Moral Development of the Children of Working and Non-Working Mothers: A Comparative Study - Javed, Muhammad Arshad; Batool, Rehana; Zahra, Annam (Annals of Human and Social Sciences, 2023)
The main objective of this study was to compare the level of moral development of the children of working and non-working mothers. There were 501 grade 7th students studying in 30 Government girls elementary schools situated in tehsil Dera Ghazi Khan. 224 students were selected as a sample of this study through cluster random sampling technique. A moral development scale (MDS) was developed in order to determine the level of moral development in the children of working and non-working mothers. It was concluded that the level of moral development in the children of working mothers was found just satisfactory as compared to the level of moral development in the children of non-working mothers which was found better. The study recommended that mothers, especially working mothers should focus on the moral development of their children.